Loss of balancing selection in the βS globin locus - Ishag Hani B; Khalil Eltahir AG; Elhassan Ibrahim M; Elzein Abeir M; Almugtaba Ibrahim A; Hussain Ayman A; Salih Niven A; Mohammed Hiba S; Kwiatkowski Dominic; Ibrahim Muntaser E (BMC, 2010)
Abstract Background Probably the best example of the rise and maintenance of balancing selection as an evolutionary trend is the role of S-haemoglobin (HbS - rs334) in protecting from malaria. Yet, the dynamics of such a process remains poorly understood, particularly in relation to different malaria transmission rates and the genetic background of the affected populations. Methods We investigated the association of haemoglobin HbS in protection from clinical episodes of malaria in two populations/villages where malaria is endemic, but mostly presenting in mild clinical forms. Five-hundred and forty-six individuals comprising 65 and 82 families from the Hausa and Massalit villages respectively were genotyped for HbS. Allele and genotype frequencies as well as departure from Hardy-Weinberg Equilibrium were estimated from four-hundred and seventy independent genotypes across different age groups. Age-group frequencies were used to calculate the coefficient-of-fitness and to simulate the expected frequencies in future generations. Results Genotype frequencies were within Hardy-Weinberg expectations in Hausa and Massalit in the total sample set but not within the different age groups. There was a trend for a decrease of the HbS allele frequency in Hausa and an increase of frequency in Massalit. Although the HbS allele was able to confer significant protection from the clinical episodes of malaria in the two populations, as suggested by the odds ratios, the overall relative fitness of the HbS allele seems to have declined in Hausa. Conclusions Such loss of balancing selection could be due to a combined effect of preponderance of non-clinical malaria in Hausa, and the deleterious effect of the homozygous HbS under circumstances of endogamy.